Relations between Belgrade and Priština: From technical to political dialogue - Đukanović Dragan (Međunarodni Problemi, 2013)
In this article, the author deals with the dialogue process between the authorities in Belgrade and Priština after the unilateral proclamation of Kosovo’s independence in 2008. He analyses the genesis and ranges of this technical and political dialogue between Belgrade and Priština from 2011 and all agreements (freedom of movement, personal documents, customs, cadastre, mutual recognitions of the university diplomas, Integrated Border Management, representation of Kosovo in the regional integrations and forums) with special emphasis on the “First agreement of principles governing the normalization of relations” (Brussels, 19 April 2013) and the creation of the Association/Community of Serb Majority Municipalities in Kosovo. He concludes that the dialogue between Belgrade and Priština has been the major political success of the European Union within the frameworks of mechanism of the Common Foreign and Security Policy. The author also gives some predictions concerning the next steps in the dialogue between Belgrade and Priština also presenting potential “neuralgic” topics (ethnic community protection, status of the Serbian Orthodox Church and property issues). [Projekat Ministarstva nauke Republike Srbije, br. OI179023: Srbija u savremenim međunarodnim integrativnim procesima – spoljnopolitički, međunarodni, ekonomski, pravni i bezbednosni aspekti i projekta i Uticaj politike uslovljavanja EU na prava i zaštitu manjina u Slovačkoj i Srbiji]